A Projcet report on Distributed cut Detection in Wireless Sensor Networks - SAHANA S, PRIYA M and SHHRUTHI D (2014)
INTERNAL GUIDE: Mr. AVANTIKA CHHIBBAR, MVJCE CD ONLY
Keywords: cut Detection in Wireless Sensor Networks